2020
DOI: 10.20870/oeno-one.2020.54.4.4501
|View full text |Cite
|
Sign up to set email alerts
|

Detection of smoke-derived compounds from bushfires in Cabernet-Sauvignon grapes, must, and wine using Near-Infrared spectroscopy and machine learning algorithms

Abstract: The number and intensity of wildfires are increasing worldwide, thereby raising the risk of smoke contamination of grapevine berries and the development of smoke taint in wine. This study aimed to develop five artificial neural network (ANN) models from berry, must, and wine samples obtained from grapevines exposed to different levels of smoke: (i) Control (C), i.e., no misting or smoke exposure; (ii) Control with misting (CM), i.e., in-canopy misting, but no smoke exposure; (iii) low-density smoke treatment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…For example, research by Summerson et al [5] developed ANN models that accurately classified either berry (Model 1: 98.00% overall accuracy) or leaf (Model 2: 97.40% overall accuracy) NIR readings according to the different smoke treatments applied. Furthermore, several studies have demonstrated great success in predicting levels of smoke-derived volatile phenols and their glycoconjugates in grapes and wine using NIR spectroscopy and ANN modeling [6,88]. A study by Fuentes et al [88] developed a model that accurately predicts levels of guaiacol glycoconjugates in berries as well as guaiacol and guaiacol glycoconjugates for seven different grapevine cultivars using NIR berry measurements between 700 and 1100 nm.…”
Section: Current and Emerging Methods Of Assessing Grapevine Smoke Contamination And Smoke Taint In Winementioning
confidence: 99%
See 4 more Smart Citations
“…For example, research by Summerson et al [5] developed ANN models that accurately classified either berry (Model 1: 98.00% overall accuracy) or leaf (Model 2: 97.40% overall accuracy) NIR readings according to the different smoke treatments applied. Furthermore, several studies have demonstrated great success in predicting levels of smoke-derived volatile phenols and their glycoconjugates in grapes and wine using NIR spectroscopy and ANN modeling [6,88]. A study by Fuentes et al [88] developed a model that accurately predicts levels of guaiacol glycoconjugates in berries as well as guaiacol and guaiacol glycoconjugates for seven different grapevine cultivars using NIR berry measurements between 700 and 1100 nm.…”
Section: Current and Emerging Methods Of Assessing Grapevine Smoke Contamination And Smoke Taint In Winementioning
confidence: 99%
“…A study by Fuentes et al [88] developed a model that accurately predicts levels of guaiacol glycoconjugates in berries as well as guaiacol and guaiacol glycoconjugates for seven different grapevine cultivars using NIR berry measurements between 700 and 1100 nm. In further research, Summerson et al [6] developed five different models that displayed high accuracy in predicting levels of volatile phenols and their glycoconjugates in Cabernet Sauvignon grapes and wine. The first three models were developed using NIR berry spectra taken one day after grapevine smoke exposure as inputs to predict levels of 10 volatile phenols and 18 glycoconjugates in grapes at either one day after smoke exposure (Model 1: R = 0.98; R 2 = 0.97; b = 1) or harvest (Model 2: R = 0.98; R 2 = 0.97; b = 0.97), as well as six volatile phenols and 17 glycoconjugates in the final wine (Model 3: R = 0.98; R 2 = 0.95; b = 0.99).…”
Section: Current and Emerging Methods Of Assessing Grapevine Smoke Contamination And Smoke Taint In Winementioning
confidence: 99%
See 3 more Smart Citations